Avaliação da aprendizagem da pessoa com deficiência intelectual: análise de teses e dissertações brasileiras - Alves, Augusto Marques (2018)
The present research focuses on the schooling of people with disabilities, especially the school evaluation of students with intellectual disabilities. The evaluation of school learning aims to diagnose the elements that are contributing and / or hindering learning and help in its improvement. The evaluation actions within the classroom reflect not only in the way of conceiving and applying the evaluation, but also in the schooling of students with and without disabilities. In this direction we must ask ourselves: How are teachers of the regular classroom, Elementary School, performing evaluations of school learning for their students with intellectual disabilities? What does Brazilian academic production reveal to us? The present research had as general objective to make a balance and analysis of the Brazilian academic production on the evaluation of the school learning of students with intellectual deficiency, enrolled in common classroom of the Elementary School. It is a systematic review of literature supported by the methodology of integrative bibliographical research. The results indicate that the number of academic researches that have the evaluation of the learning of students with intellectual disabilities in the regular classroom of Elementary School as an object of research and analysis is small; showed the concomitant occurrence of different conceptions about the intellectual deficiency and evaluation of the learning of these students; that teachers indicate that forms of evaluation are more than documents for the purpose of recording students' performance in the learning of school contents and recognize that the evaluation tools used have an important role. These were the data selected and analyzed by this research and may indicate a transition phase in the way of conceiving intellectual disability in the classroom and how to assess the learning of these students.